(untitled) (European Journal of Pure and Applied Mathematics, 2022)
This paper deals with the concepts of upper and lower contra-(Λ, sp)-continuous multifunctions. Moreover, some characterizations of upper and lower contra-(Λ, sp)-continuous multifunctions are investigated.